Slip-draft embedded control system by adaptively adjusting the battery position for electric tractors - Wang, Minghui; Ning, Pucai; Su, Ke; Yoshinori, Gejima; Wang, Wei; Cui, Yongjie; Cui, Gongpei (International Journal of Agricultural and Biological Engineering, 2023)
A slip-draft embedded control system was designed and developed for an independent developed 2WD (two-wheel drive) electric tractor, to improve the traction efficiency, operation performance and ploughing depth stability of the electric tractor. In this system, the battery of electric tractor was innovatively equivalent to the original counterweight of the fuel tractor. And through dynamic analysis of electric tractor during ploughing, the mathematical model of adjusting the center of gravity about draft force and slip rate was established. Then the automatic adjustment of the center of gravity for electric tractor was realized through the adaptive adjustment of battery position. Finally, the system was carried on electric tractor for performance evaluation under different ploughing conditions, the traction efficiency, slip rate and front wheel load of electric tractor were measured and controlled synchronously to make it close to the set range. And the comparative experiments of ploughing operation were carried out under the two modes of adaptive adjustment of center of gravity and fixed center of gravity. The test results showed that, based on the developed control system, the center of gravity of electric tractor can be adjusted in real time according to the complex changes of working conditions. During ploughing operation with adjusting adaptively battery position, the average values of traction efficiency, slip rate, front wheel load and relative error of tillage depth of electric tractor were 64.5%, 22.2%, 2045.0 N and 2.0% respectively. Which were optimized by 15.0%, 29.5%, 19.6% and 80.0% respectively, compared with electric tractor with fixed battery position. The slip-draft embedded control system can not only realize the adaptive adjustment of the center of gravity position in the ploughing process of electric tractor, but also improve the traction efficiency and the stability of ploughing depth, which can provide reference for the actual production operation of electric tractor.Key words: electric tractor, embedded control system, adjusting adaptively, center of gravity position, performance testDOI: 10.25165/j.ijabe.20231605.7280Citation: Wang M H, Ning P C, Su K, Yoshinori G, Wang W, Cui Y J, et al. Slip-draft embedded control system by adaptively adjusting the battery position for electric tractors. Int J Agric & Biol Eng, 2023; 16(5): 155-164.